2005
DOI: 10.1143/jjap.44.4625
|View full text |Cite
|
Sign up to set email alerts
|

Bubble Generation by Standing Wave in Water Surrounded by Cranium with Transcranial Ultrasonic Beam

Abstract: Low-frequency ultrasound, typically less than 1 MHz, is suitable for enhancing thrombolysis because it penetrates the cranium effectively. However, intracerebral hemorrhages after transcranial insonation in clinical trials at 300 Hz have been reported. In this study, acoustic bubble formation in a standing wave with a 617 kHz ultrasonic beam in water surrounded by a contoured piece of a human cranium was detected by ultrasound B-mode imaging. This bubble formation was indirect evidence that standing-wave forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 24 publications
0
32
1
Order By: Relevance
“…Using an optical technique, Azuma et al (2005) observed similar acoustic patterns attributed to standing waves. We postulate that hemorrhages noted clinically in the contralateral, in clinical trials of ultrasound enhanced thrombolysis, might be due to such standing waves (Daffertshofer et al 2005;Reinhard et al 2006;Wilhelm-Schwenkmezger et al 2007).…”
Section: Discussionmentioning
confidence: 82%
“…Using an optical technique, Azuma et al (2005) observed similar acoustic patterns attributed to standing waves. We postulate that hemorrhages noted clinically in the contralateral, in clinical trials of ultrasound enhanced thrombolysis, might be due to such standing waves (Daffertshofer et al 2005;Reinhard et al 2006;Wilhelm-Schwenkmezger et al 2007).…”
Section: Discussionmentioning
confidence: 82%
“…In addition, the transducers used in the animal experiments by Schneider et al [15] and by Reuter et al [18] were also relatively large (350 mm 2 , about 17.5-fold higher than the LFTUS in the present study). These large transducers result in delivery of much more acoustic energy into the intracranial cavity and increase the formation of dangerous standing waves near the opposite cranium [10,30]. Third, the frequency (≈500 kHz) of our LFTUS was higher than those used in other LFTUS studies (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The upper limit of the duration time was decided to avoid the effect of standing wave components-for instance, those caused by reflections between a HIFU transducer and HIFU focus or skin surface. This was under the consideration that standing wave components tend to decrease the cavitation threshold [47,48] and may make it difficult to locally generate bubble Appl. Sci.…”
Section: Trigger Hifu Sequencementioning
confidence: 99%